ANALISIS KESALAHAN MENULIS UNSUR KEBAHASAAN DALAM TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 4 SOMAMBAWA - Ndruru, Krisman Berkat Saputra (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research aimed to describe the students’ mistakes and the factors cause of students’ mistakes in using language features in explanation text. This research used the qualitative research with descriptive approach. The data in this research were the language features and the statements related with the factors causes of the students’ mistakes in using language features in within a explanation text. the source of data in this research were obtained from the exposition text as students’ worksheet and the results of interview to the teacher and students. Then, the data analysis techniques were used in this research, by using data reduction, data display and drawing conclusion/verification. Based on the research finding, the eighth grade of Negeri 4 Somambawa had the mistakes in using the language features in explanation text. The students’ mistakes themselves were the using of pronoun, conjunction dan noun. The students’ mistake in using pronoun was students not be able to use pronoun appropriate with the subject in the sentences. Then, students’ mistake in using conjunction was, students not be able to connect the clauses, sentences and paragraphs in the explanation text. And, the students’ mistake in using noun was, students not be able to use noun appropriate with the situations in the sentence itself. The students’ mistakes themselves caused by the less of students’ motivation and interesting to study so the learning material is conveying by the teacher cannot be comprehended by the students. As suggestions, the results of this research expected can be as the considering for the teacher to improve the learning process quality in Indoenesia language subject, especially in explanation text material in the eighth grade. And, for the students, expected to improve the motivation in learning and the knowledge about the language features are used in the explanation text.